Deep'n as it come : the 1927 Mississippi River flood - Daniel, Pete (University of Arkansas Press, 1996)
The spring and summer of 1927, the Mississippi River and its tributaries flooded from Cairo, Illinois, to New Orleans, Louisiana, and the Gulf of Mexico, tearing through seven states, sometimes spreading out to nearly one hundred miles across. Pete Daniel's Deep'n as It Come, available again in a new format, chronicles the worst flood in the history of the South and re-creates, with extraordinary immediacy, the Mississippi River's devastating assault on property and lives. Daniel weaves his narrative with newspaper and firsthand accounts, interviews with survivors, official reports, and over 140 contemporary photographs. The story of the common refugee who suffered most from the effects of the flood emerges alongside the details of the massive rescue and relief operation - one of the largest ever mounted in the United States. The title, Deep'n as It Come, is a phrase from Cora Lee Campbell's earthy description of the approaching water, which, Daniel writes, "moved at a pace of some fourteen miles per day," and, in its movement and sound, "had the eeriness of a full eclipse of the sun, unsettling, chilling." "The contradictions of sorrow and humor ... death and salvation, despair and hope, calm and panic - all reveal the human dimension" in this compassionate and unforgettable portrait of common people confronting a great natural disaster